Genetic liability for diet-derived circulating antioxidants, oxidative stress, and risk of osteoarthritis: a Mendelian randomization study - Tang, Yidan; Xu, Xiaolin; Zhang, Shuangyi; Kong, Weishuang; Zhang, Weiyi; Zhu, Tao (Frontiers in Nutrition, 2023)
Background Although well-documented, the causal relationships between diet-derived circulating antioxidants, oxidative stress, and osteoarthritis (OA) are equivocal. The objective of this study is to employ two-sample Mendelian randomization (MR) to investigate possible causal relationships among dietary-derived circulating antioxidants, oxidative stress damage indicators, and OA risk. Methods Single-nucleotide polymorphisms for diet-derived circulating antioxidants (ascorbate, β-carotene, lycopene, retinol, and α-and γ-tocopherol), assessed as absolute levels and metabolites, as well as oxidative stress injury biomarkers (GSH, GPX, CAT, SOD, albumin, and total bilirubin), were retrieved from the published data and were used as genetic instrumental variables. Summary statistics for gene–OA associations were obtained from publicly available and two relatively large-scale GWAS meta-analyses to date. The inverse-variance weighting method was utilized as the primary MR analysis. Moreover, multivariable MR was used to determine if mediators (BMI and smoking) causally mediated any connection. Furthermore, for each exposure, MR analyses were conducted per outcome database and then meta-analyzed. Results Genetically predicted absolute retinol level was causally associated with hip OA risk [odds ratios (ORs) = 0.40, 95% confidence interval (CI) = 0.24–0.68, FDR-corrected p = 0.042]. Moreover, genetically predicted albumin level was causally associated with total OA risk (OR = 0.80, 95% CI = 0.75–0.86, FDR-corrected p = 2.20E-11), as well as the risk of hip OA (OR = 0.75, 95% CI = 0.68–0.84, FDR-corrected p = 1.38E-06) and knee OA (OR = 0.82, 95% CI = 0.76–0.89, FDR-corrected p = 4.49E-06). In addition, MVMR confirmed that the effect of albumin on hip OA is independent of smoking initiation, alcoholic drinks per week, and moderate-to-vigorous physical activity levels but may be influenced by BMI. Conclusion Evidence from our study supports a potentially protective effect of high levels of retinol and albumin on OA risk.